Application of human stem cell-derived cardiomyocytes in safety pharmacology requires caution beyond hERG. - Jonsson, M; Vos, M; Mirams, G; Duker, G; Sartipy, P; de Boer, T; van Veen, T (2012)
Human embryonic stem cell-derived cardiomyocytes (hESC-CM) have been proposed as a new model for safety pharmacology. So far, a thorough description of their basic electrophysiology and extensive testing, and mechanistic explanations, of their overall pro-arrhythmic ability is lacking. Under standardized conditions, we have evaluated the sensitivity of hESC-CM to proarrhythmic provocations by blockade of hERG and other channels. Using voltage patch clamp, some ion current densities (pA/pF) in hESC-CM were comparable to adult CM: I(Kr) (-12.5 ± 6.9), I(Ks) (0.65 ± 0.12), I(Na,peak) (-72 ± 21), I(Na,late) (-1.10 ± 0.36), and I(Ca,L) (-4.3 ± 0.6). I(f) density was larger (-10 ± 1.1) and I(K1) not existent or very small (-2.67 ± 0.3). The low I(K1) density was corroborated by low KCNJ2 mRNA levels. Effects of pro-arrhythmic compounds on action potential (AP) parameters and provocation of early afterdepolarizations (EADs) revealed that Chromanol293B (100 μmol/l) and Bay K8644 (1 μmol/l) both significantly prolonged APD(90). ATX-II (<1 μmol/l ) and BaCl(2) (10 μmol/l ) had no effect on APD. The only compound that triggered EADs was hERG blocker Cisapride. Computer simulations and AP clamp showed that the immature AP of hESC-CM prevents proper functioning of I(Na)-channels, and result in lower peak/maximal currents of several other channels, compared to the adult situation. Lack of functional I(K1) channels and shifted I(Na) channel activation cause a rather immature electrophysiological phenotype in hESC-CM, and thereby limits the potential of this model to respond accurately to pro-arrhythmic triggers other than hERG block. Maturation of the electrical phenotype is a prerequiste for future implementation of the model in arrhythmogenic safety testing.